Clinical handover practices among healthcare practitioners in acute care services: A qualitative study. Issue 1 (28th August 2018) - Fealy, Gerard; Donnelly, Suzanne; Doyle, Gerardine; Brenner, Maria; Hughes, Mary; Mylotte, Elaine; Nicholson, Emma; Zaki, Marina
Abstract: Aims and objectives: To examine clinical handover practices in acute care services in Ireland. Objectives were to examine clinical handover practices between and within teams and between shifts, to identify resources and supports to enhance handover effectiveness and to identify barriers and facilitators of effective handover. Background: Clinical handover is a high‐risk activity, and ineffective handover practice constitutes a risk to patient safety. Evidence suggests that handover effectiveness is achieved through staff training and standardised handover protocols. Design: The study design was qualitative‐descriptive using inductive analysis. Methods: The study involved a series of focus group discussions and interviews among a sample of healthcare practitioners recruited from 12 urban and regional acute hospitals in Ireland. A total of 116 healthcare professionals took part in 28 interviews and 13 focus group discussions. We analysed the data using the directed content analysis method. Results: Data collection generated rich qualitative data, yielding five categories from which two broad themes emerged: "policy and practice" and "handover effectiveness." The themes and their associated categories indicate that there is limited organisational‐level policy and limited explicit training in clinical handover, that medical and nursing handovers are separate activities with somewhat different purposes and different modes of execution, and that several factors in the acute care setting, including location, timing and documentation, act as either barriers or enablers to handover effectiveness. Conclusion: The evidence in the current study suggests that clinical handover merits increased level of prominence in hospital policies or operating procedures. Medical and nursing handover practices represent distinct activities in their content and execution that may be related to cultural and organisational factors. Relevance to clinical practice: Achieving multidisciplinary team handover requires a change in embedded traditional practices. Several aspects of the clinical handover activities of nursing and medical staff appear to diverge from best‐practice evidence.